Medios de comunicación digital y la identidad cultural en los habitantes del Recinto El Pechiche, cantón Ventanas, año 2019 - Zurita Bustamante, Trini Stefania (2020)
The present research project will be developed in the El Pechiche enclosure belonging to the Ventanas canton, focusing on digital media in the cultural identity of the aforementioned entity, starting from the non-conformity of the citizenry regarding the content they disseminate which they lack of cultural aspects, dedicated to sensationalism and current affairs, leaving aside enriching issues with significance in values and culture to promote good habit in the citizens of the area. The structuring of the research project and final report will be comprised of four chapters, in which important aspects of the project will be detailed with the theme to be investigated. In the first chapter, the topic to be investigated based on their respective contexts will be announced, raising appropriate objectives to solve the problem by defining their variables for the development of research. Chapter two will be framed in their respective theoretical and bibliographic support backed by the most representative authors attached to the problem being investigated to support the hypotheses of the case, in addition chapter three will detail the results of the research represented through tables and graphs Statisticians for correct interpretation and analysis. Consequently, chapter four will establish the alternative proposal to solve the problem raised during the development of the research, with the purpose of applying a guide with instructional workshops, in addition to the appropriate conclusions and recommendations.